STUDY OF THE INFLUENCE OF INFRARED RADIATION ON THE EFFECTIVENESS OF COMPLEX TREATMENT OF MANDIBULAR FRACTURES USING MICROBIOLOGICAL METHODS - Rakhimov Zokir Kayumovich (The Bioscan, 2025)
Purpose of the study. This study is aimed at revealing the microbiological effectiveness of using infrared radiation in the complex therapy of patients with mandibular fractures in order to prevent inflammatory complications. To fulfil this objective, 105 patients with diagnosed uncomplicated mandibular fractures without concomitant pathologies and 15 healthy volunteers were examined. The study participants were divided into two groups: a control group consisting of 50 patients with mandibular fractures who were treated with standard therapy and a main group consisting of 55 patients who were treated with infrared laser radiation. In all patients with fractures of the jaw a comparative analysis of the microflora composition with the microflora indicators of healthy people was carried out. In addition, dynamic microbiological studies were performed in patients suffering from mandibular fractures during the observation period (1, 7, 14 and 30 days). Results. Patients with jaw fractures showed an increased prevalence of microorganisms in the oral cavity compared to healthy individuals. Escherichia coli and fungi of the genus Candida were detected in all areas of the oral cavity examined, while Klebsiella were found in only two of the four areas (gingival and tongue). When infrared radiation was added to the standard treatment of patients with jaw fractures, no S. aureus was detected by the 30 th day of observation, in contrast to the control group, and a decrease in the number of S. mitis and S. mutans was observed. Conclusion. The obtained positive results of microbiological studies conducted in the process of dynamic monitoring of treatment give confidence in the expediency of wide application of infrared irradiation within the framework of complex pathogenetic therapy of traumatic injuries of the mandible in order to prevent infectious-inflammatory complications.